The Evidence for Adjunctive Facelift Procedures - Urso-Baiarda, Fulvio; Edmondson, Sarah-Jayne; Grover, Rajiv (Facial Plastic Surgery, 2018)
Facelift surgery is a popular treatment but exhibits high variation among practitioners in terms of both core technique and adjunctive measures. This review identified significant evidence addressing the role of pre-infiltration, drains, fat grafting, fibrin tissue adhesives, hilotherapy, and other miscellaneous adjuncts. Based on the authors' assessment of the current literature, there is reasonable supportive evidence for pre-infiltration, fat grafting and laser skin resurfacing, which appear to be safe and effective in appropriately selected patients. Drain use is not mandatory but may confer some benefit. Conversely the evidence for the use of fibrin tissue adhesives and hilotherapy is not compelling.
Keywords: adjuncts; evidence; facelift; fat graft; rhytidectomy